Argentinean validation of the Rape Supportive Attitude Scale - Alladio, Yanina (2017)
The tolerant attitudes towards sexual violence against women constitute an important risk factor that should be considered to explain this type of aggressive behavior. One of the instruments that evaluates these attitudes is the Rape Supportive Attitude Scale (RSAS) developed by Lottes. The results of different psychometric studies have demonstrated good indexes of reliability and validity in American, Spanish and Salvadorian university students. The purpose of the study was to explore the psychometric properties of the RSAS in Argen tinean university students. We provide evidence of content validity through expert ratings, process validity through cognitive debriefing interviews, and evidence of internal structure through exploratory and confirmatory factor analysis. Finally, the internal consistency of the scale was estimated and an analysis of contrasting groups in relation to gender was con ducted. The results allow us to infer that the RSAS scale is a valid and reliable tool to assess rape supportive attitudes in Argentinean university students.